Prevalence of visits by patients with persistent deciduous teeth at Puskesmas Kerambitan II from October 2024 to March 2025: Prevalensi kunjungan pasien dengan gigi sulung persisten di Puskesmas Kerambitan II dari Oktober 2024 hingga Maret 2025 - I Putu Dika Diwangga Putra; I Wayan Agus Wirya; Ni Putu Ary Wahyu Suryani (Makassar Dental Journal, 2026)
One of the most common disorders is persistent primary teeth, where the primary teeth do not fall out on time even though the teeth have grown in. There are many variations in the timing of tooth eruption. This study discusses the prevalence of persistent primary teeth at the Kerambitan II Tabanan Community Health Centre from October 2024 to March 2025. This descriptive observational study was conducted at the Kerambitan II Tabanan CHC, October 2024 to March 2025. Data were collected from patient visit records, a total of 731 visits and 234 patients with persistent deciduous teeth at the Dental Clinic; 135 females and 99 males. The prevalence of persistent primary teeth cases was 32% of total visits. The highest number of cases was in December 2024 (43.04%). It was concluded that persistent primary teeth were the most dominant case at the Kerambitan II CHC Dental Clinic during the study period.